Parental mediation and adolescent internet addiction: The role of parent-child relationship and parental internet addiction - Sikang Zhang; Zengquan Fang; Xuejing Qi; Ying Yuan (Acta Psychologica, 2025)
Prior research has consistently shown a negative association between parental mediation and adolescent internet addiction. However, this study provides new evidence suggesting that the relationship between the two may be more complex, exhibiting both protective and potentially adverse associations—a “double-edged sword” pattern. Using data from an online survey of 8182 Chinese adolescents, we found that although stricter parental mediation is directly associated with lower levels of adolescent internet addiction, it may also be negatively associated with the parent–child relationship. A poorer parent–child relationship, in turn, is linked to higher levels of adolescent internet addiction. Furthermore, parental internet addiction moderated the association between the parent-child relationship and adolescent internet addiction. These findings contribute to the literature by uncovering the dual associations between parental mediation and adolescent internet addiction and highlight the importance of improving parent-child relationships and addressing parental internet addiction to maximize the benefits of parental mediation.